The National SOM Survey 1995 - SOM Institute, University of Gothenburg (University of Gothenburg, 1997)
Since 1986 the research project ´Samhälle Opinion Massmedia´ (SOM) has been carrying out an annual nation-wide survey of Swedish opinions. This is accordingly the tenth survey in this series. The questionnaire was divided into six subject fields: mass media; politics and society; energy, nuclear power and environment; Sweden and the rest of the world; leisure; and background. Most of the questions are replications of questions asked in one or several previous SOM-surveys. New questions dealt with: the importance of 37 different subject fields in a morning paper; local advertisement papers and other local papers containing news and offered free of charge; opinion on the Swedish EU membership; the influence of finance market on politics; opinion on a number of propositions how to improve the Swedish economy; confidence in the way work is done by a number of occupational groups; confidence in different groups in regard to environmental information; opinion on how much a number of measures could contribute to a better environment in Sweden. The respondents also had to state how often they used to take a walk, ride a bike, travel by public transport, and go by car during the last month, and what they were prepared to do personally for a better environment in their municipality. Other questions dealt with how much the respondent read from different contents of a morning paper. The respondent was also asked about the participation in the first Swedish election to the EU-parliament in the fall of 1995, kind of ballot used, and if the possibility to vote on a specific person was used.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den tionde undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

1995 års undersökning består av sex sammanhållna delar: massmedier; politik och samhälle; Sverige och omvärlden; energi, kärnkraft och miljö; fritid och boende; samt bakgrundsfrågor. Genom att frågor ställts på ett likartat sätt över tid finns det i SOM-serien tidsserier om bland annat medieanvändning, politik, kärnkraftsopinion och förtroende för olika samhällsinstitutioner och grupper.

Nya frågeställningar i denna undersökning gäller bland annat 37 olika ämnesområdens betydelse i en morgontidning; läsning av lokala annonsblad och lokala gratistidningar som innehåller nyheter; inställning till det svenska EU-medlemskapet; finansmarknadens inflytande på politiken; inställning till ett antal förslag hur den svenska ekonomin skall förbättras; förtroende för det sätt ett antal yrkesgrupper sköter sitt arbete; förtroende för olika grupper när det gäller miljöinformation; inställning till hur ett antal åtgärder kan bidra till en bättre miljö i Sverige. Respondenterna fick även ange hur ofta man under den senaste månaden promenerat, cyklat, åkt kollektivt, kört eller åkt bil. De fick även uppge i vilken utsträckning de själva var beredda att göra ett antal saker för att förbättra miljön i hemkommunen. Andra frågor tog upp hur mycket respondenten normalt läser av olika typer av innehåll i den lokala morgontidningen. Respondenterna tillfrågades också om hur de röstat i det första svenska valet till EU-parlamentet hösten 1995, vilken typ av valsedel man använt och om man utnyttjat möjligheten att personrösta.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 1995
Riks-SOM 1995
Keywords: elections; val; mass media; massmedia; population migration; migration; participation; deltagande; public sector; offentlig sektor; international relations; internationella relationer; energy; energi; environment; miljö; environmental degradation; miljöförstörelse; trust; förtroende; european union; europeiska unionen; local government services; kommunal service; nuclear energy; kärnkraft; information sources; informationskällor; television channels; tv-kanaler; television news; tv-nyheter; radioactive wastes; radioaktivt avfall; equipment; utrustning; privatization; privatisering; financial markets; finansmarknad; euthanasia; dödshjälp; republic; republik; recycling; återvinning; internal politics; inrikespolitik; political parties; politiska partier; political leaders; politiska ledare; leisure time activities; fritidsaktiviteter; refugees; flyktingar; public health risks; hälsorisker; wind energy; vindenergi; radio listening; radiolyssnande; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap